Christ, the Divine Gardener: A New Look on the Risen - Martínez, Adriana M. (Eikón / Imago, 2019)
The representation of the Noli me tangere, the appearance of the risen Christ to Mary Magdalene, appears in the Latin West during the 9 th and 10 th centuries. The scene brings two Angels at the empty tomb, the Magdalene and the risen Christ. In the successive centuries is chosen to focus the subject only in the two main characters, hurting women and Christ carrying a banner with the cross. To the trecento in this Pascual scene occurs a semantic sheft to grant to the risen son of God the appearance of a gardener who us questions about the reasons for this change.